A pathogenic integrated view explaining the different endotypes of asthma and allergic disorders. Issue 11 (3rd August 2022) - Maggi, Enrico; Parronchi, Paola; Azzarone, Bruno Giuseppe; Moretta, Lorenzo
Abstract: The inflammation of allergic diseases is characterized by a complex interaction between type 2 and type 3 immune responses, explaining clinical symptoms and histopathological patterns. Airborne stimuli activate the mucosal epithelium to release a number of molecules impacting the activity of resident immune and environmental cells. Signals from the mucosal barrier, regulatory cells, and the inflamed tissue are crucial conditions able to modify innate and adaptive effector cells providing the selective homing of eosinophils or neutrophils. The high plasticity of resident T‐ and innate lymphoid cells responding to external signals is the prerequisite to explain the multiplicity of endotypes of allergic diseases. This notion paved the way for the huge use of specific biologic drugs interfering with pathogenic mechanisms of inflammation. Based on the response of the epithelial barrier, the activity of resident regulatory cells, and functions of structural non‐lymphoid environmental cells, this review proposes some immunopathogenic scenarios characterizing the principal endotypes which can be associated with a precise phenotype of asthma. Recent literature indicates that similar concepts can also be applied to the inflammation of other non‐respiratory allergic disorders. The next challenges will consist in defining specific biomarker(s) of each endotype allowing for a quick diagnosis and the most effective personalized therapy.